Factores organizacionales y recursos humanos que afectan la calidad de atención y seguridad del paciente en servicios de emergencia en hospitales de países en vías de desarrollo: scoping review - Vidal Córdova, Nathalie Valeria (2025)
Within the emergency departments of healthcare institutions in developing countries, a variety of organizational and human resource challenges have been identified that directly affect the quality of care and patient safety. These factors significantly interfere with achieving positive outcomes that lead to patient satisfaction. The objective of this research was to explore the available evidence and describe the organizational and human resource factors that impact the quality of care and patient safety in emergency services in hospitals located in developing countries. A literature review was conducted using a scoping review methodology, guided by PRISMA-ScR extension guidelines. Articles were searched in well-known databases such as Scopus, SciELO, and PubMed, considering inclusion and exclusion criteria, within the time frame of 2014 to 2024, and in both English and Spanish. Relevant data were manually extracted and subjected to thematic analysis. A total of 30 articles were included, which yielded four main themes: 1. Organizational factors that determine the quality of care and patient safety in emergency settings; 2. Human resource factors that generate issues and negatively affect the quality of care and patient safety in emergency departments; 3. Consequences of these organizational and human resource factors in emergency units in developing countries; 4. Strategies employed to improve the quality of care and patient safety. In conclusion, all of these factors and their interrelations negatively influence emergency departments, creating environments with a higher risk of adverse events that compromise care quality and patient safety. Therefore, it is crucial to emphasize quality and safety improvement strategies through appropriate organizational activities and effective management in healthcare institutions and related areas, in order to ensure efficient care, especially in developing countries.